De Novo Collapsing Glomerulopathy: An Unusual Cause of Early Graft Failure following Kidney Transplantation - Kalathil K. Sureshkumar; Imran Dosani; Katherine M. Jasnosz; Swati Arora (Case Reports in Transplantation)
Collapsing glomerulopathy (CG) is a variant of focal segmental glomerulosclerosis (FSGS) characterized histologically by prominent glomerular capillary tuft collapse with hypertrophy and hyperplasia of podocytes and tubulointerstitial damage. Patients usually present with heavy proteinuria and rapidly progressive renal failure. We report a patient who developed de novo CG with severe clinical manifestations including worsening renal failure and nephrotic syndrome within six months of receiving deceased donor kidney transplant. Secondary work-up was negative, and despite therapy with high-dose steroids and plasmapheresis, allograft function rapidly deteriorated with the need for dialysis. Theories about the pathogenesis of this entity as well as treatment modalities are discussed.